The Relationship Between Nutritional Status and The Incidence of Hypertension in the Elderly in Kekeran Village, Mengwi District, Badung Regency, Bali - Ni Putu Sinta Maharani; Luh Putu Lina Kamelia; Ni Nyoman Mestri Agustini (International Journal of Health Engineering and Technology, 2025)
This study aims to analyze the relationship between nutritional status and the incidence of hypertension among elderly people in Kekeran Village, Mengwi District, Badung Regency, Bali. This study uses an observational analytical method with a cross-sectional research design. The results show that most elderly people in Kekeran Village are overweight, accounting for 53.15% of the total respondents. Meanwhile, 20.28% of the elderly were underweight, 18.18% had normal nutritional status, and 8.39% were obese. This condition illustrates that being overweight is still a prominent nutritional problem among the elderly in this region. Based on blood pressure distribution, most respondents were classified as having stage I hypertension (39.16%), followed by prehypertension (36.36%), stage II hypertension (18.88%), and only 5.59% of the elderly had normal blood pressure. This indicates that high blood pressure remains a fairly common health problem among the elderly in Kekeran Village. The results of the analysis using Spearman's rank correlation test showed a significant relationship between nutritional status and the incidence of hypertension in the elderly in Kekeran Village with a p-value of 0.003 (p < 0.05) and a correlation coefficient (r) of 0.244. This relationship is positive with weak strength, which means that an increase in nutritional status or body mass index is directly proportional to an increase in the risk of hypertension.